On the measurement of environmental taxes - Annegrete Bruvoll (Statistics Norway, Research Department, 2009)
The purpose of environmental taxes is to correct the market when it fails to take environmental damages into account, i.e. to internalize the Pigouvian element. In addition, fiscal taxes are levied on both polluting and clean goods, which may follow the Ramsey principle. In practical policy, environmental and fiscal taxes are conceptually intertwined. This mixture complicates the calculation of the extent and the evaluation of the effects of environmental taxes. Eurostat, OECD and IEA include all taxes related to energy, transport and pollution, and most resource taxes in their international measurement of environmentally related taxes. Consequently, numerous fiscal taxes are added together with the environmental taxes. This article discusses the distinctions between the Pigouvian and the fiscal taxes in light of tax theory. The revenues following the Eurostat et al. statistical basis deviate significantly from the revenues from the environmental taxes defined on the basis of theory. Steps should be taken to harmonize the international statistics of environmental taxes with economic tax theory.
Keywords: H23; Q58; 330; Environmental taxes; Fiscal taxes; Pigou taxes; Ramsey taxes